Herbivores 2017
DOI: 10.5772/67346
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Plant Defense Against Herbivores

Abstract: Herbivores can damage plant productivity and fitness because plants have improved defense mechanisms such as physical barriers, association with other organisms such as ants, and chemical defense. In that, separate plant species produce different chemical molecules. Chemical compounds involved in plant defense can act in several facts: decreased palatability, like a poison, such as a stunner, and increased gene defense expression, among others. In this chapter, we approach several examples of chemical molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 131 publications
(198 reference statements)
1
11
0
1
Order By: Relevance
“…Our results showed that the activity of peroxidase in the leaves of horse chestnut plants in August from the same experimental sites but with a higher level of damage (78.3% and 97.5%) is significantly higher (2.2 and 2.1 times, respectively) than in the leaves of relatively resistant trees with damage level 13.3%. The increase in cytoplasmic peroxidase activity caused by mechanical injury was within the range of the increase in peroxidase activity found in other plants (Singh et al, 2013;Sánchez-Sánchez & Morquecho-Contreras, 2017). The changes observed in the activity of the enzyme in phase of active outflow of assimilates indicates its active participation in metabolic processes of leaves after damage caused by phytophages.…”
Section: Discussionsupporting
confidence: 72%
“…Our results showed that the activity of peroxidase in the leaves of horse chestnut plants in August from the same experimental sites but with a higher level of damage (78.3% and 97.5%) is significantly higher (2.2 and 2.1 times, respectively) than in the leaves of relatively resistant trees with damage level 13.3%. The increase in cytoplasmic peroxidase activity caused by mechanical injury was within the range of the increase in peroxidase activity found in other plants (Singh et al, 2013;Sánchez-Sánchez & Morquecho-Contreras, 2017). The changes observed in the activity of the enzyme in phase of active outflow of assimilates indicates its active participation in metabolic processes of leaves after damage caused by phytophages.…”
Section: Discussionsupporting
confidence: 72%
“…Resin and yellow sticky traps show subtle differences, however, potentially as a result of the production of volatile compounds as chemical defenses against herbivores (22,23). In particular, the compound caryophyllene, found in African Hymenaea resin (24), acts in different species of trees as a defense against herbivores, including some ants, some termites, and various other insect orders (25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%
“…Physical deterrents include protective structural characteristics, which include waxy barriers, spikes, and “hair-like” trichomes, which release chemical compounds [ 4 ]. Chemical defense mechanisms include, for example, the production of a range of defensive metabolites bioactive compounds with the capability to repulse herbivores or even to target their endocrine and nervous system [ 5 , 6 ]. These include EOs, enzymes, tannins, and flavonoids, amongst others.…”
Section: Introductionmentioning
confidence: 99%